2004
DOI: 10.2478/bf02475575
|View full text |Cite
|
Sign up to set email alerts
|

RuO4-mediated oxidation ofN-benzylated tertiary amines. Are amineN-oxides and iminium cations reaction intermediates?

Abstract: N-Benzylmorpholine, -piperidine, and -pyrrolidine (1A-C, resp.) are oxidised by RuO4 (generated m situ) at both endocyclic and exocyclic (benzylic) N-c~ methylene positions to afford lactams (and dioxo-derivatives) and benzaldehyde (and benzoyl derivatives), respectively. The N-oxides of 1A-C, formed by a minor side reaction, are not involved as intermediates. Control experiments showed the transient formation of endo-and exocyclic iminium cations trapped with NaCN as the corresponding nitriles. The proposed c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(47 citation statements)
references
References 75 publications
2
45
0
Order By: Relevance
“…As shown below, the oxidative patterns of 1, 7, or 9 were more complicated than those suggested in the literature [6]. Generally speaking, the respective reactions followed the same pathways as those already reported by us for other substrates [7,8]. Even more interesting was the behavior of 4 and of its oxygenated derivatives; the respective results will be detailed in a coming paper [9].…”
Section: Scheme 1 Oxidation By Ruo 4 Of Piperazine Derivatives (Litermentioning
confidence: 58%
See 2 more Smart Citations
“…As shown below, the oxidative patterns of 1, 7, or 9 were more complicated than those suggested in the literature [6]. Generally speaking, the respective reactions followed the same pathways as those already reported by us for other substrates [7,8]. Even more interesting was the behavior of 4 and of its oxygenated derivatives; the respective results will be detailed in a coming paper [9].…”
Section: Scheme 1 Oxidation By Ruo 4 Of Piperazine Derivatives (Litermentioning
confidence: 58%
“…Oxidation was performed in the same conditions as above [2,3,7,8], that is with catalytic amounts of RuO 4 (generated in situ from catalytic RuO 2 and excess NaIO 4 ), in CCl 4 /water heterogeneous mixtures and at room temperature. The reaction mixtures were worked-up in two ways (A or B ; see Section 3.8), differing by the order of operations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 The identified reaction products and the corresponding yields are shown in Table 1 (entries 1-4). To understand better the behaviour of 1A-B, several control experiments were performed also and the respective results are partly listed in Table 1 (entries 5-11).…”
Section: Resultsmentioning
confidence: 99%
“…In a previous paper 1 we studied the RuO 4 -mediated oxidation 2 of some N-benzylated cycloalkylamines and found that the attack occurs at both types of N-α-methylene positions, 3 i.e., endocyclic and exocyclic (benzylic). Proof of the incursion of the corresponding iminium cations as intermediates came from their capture as nitriles in the presence of cyanide anion (cyano trapping).…”
Section: Introductionmentioning
confidence: 99%